2020
DOI: 10.1080/02589346.2020.1840026
|View full text |Cite
|
Sign up to set email alerts
|

Perpetuating Crises at the Source?: (Inter)Regionalism and Normative Incoherence for Sustainable Migration in Africa

Abstract: In response to the 2015-2016 migration crisis, the European Union established the Emergency Trust Fund for Africa that aimed 'to address the root causes of instability, forced displacement and irregular migration and to contribute to better migration management.' This article questions the logic of this approach to migration management by asking whether African regions can 'better manage migration.' The article examines the normative bases of migration policies amongst the African Union (AU) and six regional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Similarly, Carbone and Keijzer (2016) argue that the EU has pursued the development of institutional reform over policy effectiveness, highlighting again that PCD has been pursued as an end in itself rather than a means to achieve transformative development and normative change. Scholarship on PCD also recognises a “Northern” bias (Koff, 2020; Mbanda & Fourie, 2019) which limits its normative impact. All these studies clearly show the normative weakness of PCD as it has been practised to date.…”
Section: Normative Coherence For Development: a Conceptual Approachmentioning
confidence: 99%
“…Similarly, Carbone and Keijzer (2016) argue that the EU has pursued the development of institutional reform over policy effectiveness, highlighting again that PCD has been pursued as an end in itself rather than a means to achieve transformative development and normative change. Scholarship on PCD also recognises a “Northern” bias (Koff, 2020; Mbanda & Fourie, 2019) which limits its normative impact. All these studies clearly show the normative weakness of PCD as it has been practised to date.…”
Section: Normative Coherence For Development: a Conceptual Approachmentioning
confidence: 99%
“…Recent PCD literature highlights different kinds of PCD: from coherence as a policy tool, to normative statements prioritizing development co‐operation (Häbel, 2020), to recent engagements of normative PCD on sustainable development. This literature is extensive but it fails to focus on power relationships concerning the adoption of norms outside their original context (Koff, 2020). This article builds on previous arguments related to development co‐operation and water (and sustainable development in general), which focus squarely on technical aspects of service delivery to the detriment of normative positions (Koff & Maganda, 2016).…”
Section: Literature Review Of Policy Coherence For Development Power ...mentioning
confidence: 99%
“…Koff’s (2017) research on migration showed how its securitization in Europe and the Americas normatively undermines sustainable migration management because human rights tribunals have limited roles in migration governance. Koff’s (2020) study of African regional economic communities similarly illustrates how unsustainable development strategies promoting growth and free trade undermine sustainable migration management throughout the continent.…”
Section: Literature Reviewmentioning
confidence: 99%